Liposomal Drug Delivery Systems Have Opened a New Window in Pharmaceutical Sciences: A Literature-based Review - Rafe, Md. Rajdoula (Asian Journal of Pharmaceutics (AJP), 2017)
Widespread applications of liposome make it most interested carrier system of research and development than other available carrier systems. The lipids nanomedicine system was the first to make the concept of nanomedicine delivery into clinical approach that made them an established drug delivery system in present time for enormous success. In its application, liposome drug delivery usually targets directly to the tissue, which may contain target recognition molecules or not. This article is intended to give a brief overview of liposomal drug delivery system, its worldwide applications, and future perspective. Literature search results revealed applications of the liposome are in the immunology, vaccine and antigen, target delivery, delivery of insoluble or poorly drugs, delivery of nucleic acids, tumor therapy, and in combination therapy. At present, liposomal delivery is very popular in developed country, but we hope that, in future, the liposomal drug delivery system will revolutionize in all parts of the world to make the drug delivery system as perfect and effective as possible.